Preparation method of composite membrane with surface coated with cellulose, composite membrane prepared by preparation method and application of composite membrane

Through the preparation method of composite membrane with surface-coated cellulose, combined with MOF and ZnO nanoparticles, the existing membrane has solved the problems of low efficiency and poor pollution resistance in oil-water separation, and achieved efficient and stable oil-water separation and flux recovery , suitable for industrial applications.

CN119113815AActive Publication Date: 2024-12-13CHANGZHOU UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411213329.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

In the oil-water separation, existing membranes have problems such as low separation efficiency, poor pollution resistance, high viscosity, etc., such as crude oil with low separation efficiency, poor pollution resistance, and rapid flux attenuation, making it difficult to effectively treat oil-containing sewage.

Method used

Using the composite film preparation method of surface-coated cellulose, MOF is prepared by mixing DMF, ZrCl4 and H2ATA and reacting with acetic acid, adding ZnO nanoparticles to form MOF@ZnO material, and combining with polyvinylpyrrolene and cellulose, MOF is prepared @ZnO@Cellulose@PVDF composite film.

Benefits of technology

It has achieved efficient oil-water separation, strong anti-pollution performance, high flux recovery rate, low cost, and suitable for industrial applications. The interception effect of ultrafiltration membrane reaches more than 100%, and the flux is stable, far exceeding that of traditional membranes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113815A_ABST
    Figure CN119113815A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a composite membrane with the surface coated with cellulose and the composite membrane prepared through the preparation method and application of the composite membrane. The preparation method comprises the steps that MOF (at) ZnO is dispersed in N-N dimethylacetamide to be stirred, polyvinylpyrrolidone is added, stirring continues to be conducted, and ultrasonic treatment is conducted to obtain a mixed solution; a carrier is dip-coated with the membrane casting solution, and the dip-coated carrier is placed in a glass sheet and deionized water to be treated to obtain an ultrafiltration membrane; the obtained ultrafiltration membrane is put into a cellulose solution of a Tris-HCl buffer solution to be soaked, and the MOF (at) ZnO (at) Cellulose (at) PVDF composite separation membrane is obtained. The separation membrane disclosed by the invention has excellent separation efficiency and flux recovery rate on five different oil-water mixtures of kerosene, gasoline, 1, 2-dichloroethane, edible oil and normal hexane. The oil-water separation membrane provided by the invention is simple in preparation process, low in cost and mild in reaction condition, and has the advantages of high efficiency, good removal performance and good recoverability when being applied to organic wastewater separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of membrane preparation, and in particular relates to a method for preparing a composite membrane with cellulose coated on the surface, the prepared composite membrane and application thereof. Background Art

[0002] With the acceleration of industrialization worldwide, various industrial productions will produce a large amount of oily wastewater, which poses a serious threat to the ecological environment. And a major challenge to human health. Especially in oily wastewater, the impact of water-soluble pollutants such as dyes and heavy metal ions on water resources, pollution sources and the threat to the ecological environment are increasing. Conventional separation technologies such as air flotation, chemical coagulation and adsorption have been widely used. Suitable for the purification of petroleum wastewater. However, they all have their own defects, such as low efficiency and high cost. And its application in oil-water separation is discussed. In addition, this method can be used to separate stable emulsions, and can also be used to add emulsifiers. After using chemical agents, the emulsification effect is not good, resulting in high energy consumption and secondary pollution.

[0003] In recent years, the demand for materials that can effectively and quickly separate oil-water mixtures and oil-water emulsions has increased rapidly.

[0004] However, the membranes currently prepared have problems such as low separation efficiency, poor anti-pollution ability, easy clogging of pores by crude oil with high viscosity, and rapid flux decay.

[0005] Therefore, developing an oil-water separation membrane with good separation efficiency, good stability and good reusability is still an urgent problem that needs to be solved. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a composite membrane with cellulose coated on the surface.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a composite film coated with cellulose on the surface, comprising:

[0010] DMF, ZrCl4 and H2ATA were mixed, ultrasonicated, acetic acid was added, and the prepared solution was poured into an autoclave for high temperature reaction;

[0011] After the reaction is completed, the solution is centrifuged to obtain a yellow crystalline solid, which is washed with DMF and ethanol and baked at high temperature to obtain a yellow crystalline solid;

[0012] The yellow crystalline solid and ZnO nanoparticles were dispersed in an ethanol solution, ultrasonically mixed, dried, and ground to obtain MOF@ZnO material;

[0013] MOF@ZnO was dispersed in NN-dimethylacetamide and stirred, polyvinyl pyrrolidone was added and continued to stir, and ultrasonic treatment was performed to obtain a mixed solution;

[0014] Adding polyvinylidene fluoride powder into the mixed solution, stirring and mixing evenly, and standing to degas, to obtain a casting solution;

[0015] The casting solution is dip-coated on the carrier, and the dip-coated carrier is placed on a glass sheet and treated in deionized water to obtain an ultrafiltration membrane;

[0016] The obtained ultrafiltration membrane was immersed in a cellulose solution containing Tris-HCl buffer solution to obtain a MOF@ZnO@Cellulose@PVDF composite separation membrane.

[0017] As a preferred embodiment of the preparation method of the present invention, the material ratio of DMF, ZrCl4 and H2ATA is 50mL:(0.5~2mmol):(0.5~2mmol).

[0018] As a preferred embodiment of the preparation method of the present invention, the ratio of acetic acid to DMF is 5-7 mL:50 mL.

[0019] As a preferred embodiment of the preparation method of the present invention, the prepared solution is poured into an autoclave for high temperature reaction, wherein the reaction temperature is 120-125° C. and the reaction time is 12-24 hours.

[0020] As a preferred embodiment of the preparation method of the present invention, the yellow crystalline solid is obtained by high-temperature baking, wherein the treatment temperature is 80° C. and the treatment time is 10 to 12 hours.

[0021] As a preferred embodiment of the preparation method of the present invention, the yellow crystalline solid and ZnO nanoparticles are dispersed in an ethanol solution, wherein the material ratio of MOF material to ZnO is (0.1-0.9):(0.1-0.9).

[0022] As a preferred embodiment of the preparation method of the present invention, the mixed solution comprises MOF@ZnO, NN dimethylacetamide and polyvinyl pyrrolidone in a ratio of 0.1 g:40 ml:0.1 g, and the particle size of MOF@ZnO is 1300 mesh.

[0023] As a preferred embodiment of the preparation method of the present invention, the ratio of the mixed liquid to polyvinylidene fluoride is (30-50) ml: (3-4) g.

[0024] As a preferred embodiment of the preparation method of the present invention, the cellulose solution of the Tris-HCl buffer solution has a pH value of 8.5 and a cellulose concentration of 80 to 100 mg / L.

[0025] Another object of the present invention is to overcome the deficiencies in the prior art and provide a MOF@ZnO@Cellulose@PVDF composite membrane prepared by a preparation method.

[0026] Another object of the present invention is to overcome the deficiencies in the prior art and provide an application of a MOF@ZnO@Cellulose@PVDF composite membrane in oil-water separation, wherein the oil includes kerosene.

[0027] Beneficial effects of the present invention:

[0028] (1) The MOF@ZnO@Cellulose@PVDF composite membrane prepared by the method of the present invention has the characteristics of strong anti-pollution performance, obvious oil-water separation effect, simple preparation process, low preparation cost, etc., and has good commercial prospects in the field of membrane technology. The ultrafiltration membrane prepared by the present invention can achieve a retention effect of nearly 100%, and the filtration flux is about 5 times that of the original PVDF membrane, showing an excellent oil-water separation effect.

[0029] (2) The ultrafiltration membrane prepared by the method of the present invention has excellent anti-pollution ability. The results of the anti-pollution test show that the ultrafiltration membrane prepared by the method of the present invention has a flux recovery rate of nearly 100% after filtering the oil-water emulsion compared with the traditional ultrafiltration membrane (unmodified) (the unmodified ultrafiltration membrane is only 70%); at the same time, the flux attenuation rate of the modified membrane is much lower than that of the unmodified membrane, indicating that the ultrafiltration membrane of the present invention not only has a high oil-water separation efficiency, but also can achieve a high recovery rate after oil-water separation, maintain the effectiveness of its own flux, and effectively prevent pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0031] Figure 1 : is a SEM image of the composite membrane prepared in the example of the present invention.

[0032] Figure 2 The figure is a diagram showing the filtering effect of the composite membrane prepared in the embodiment of the present invention on different types of oil. DETAILED DESCRIPTION

[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0036] The ZnO nanoparticles in the present invention were purchased from Hangzhuo Metal Materials with a particle size of 20 nm; dimethylacetamide was purchased from Sinopharm Group; polyvinyl pyrrolidone (PVP-K30) of high purity was purchased from Sinopharm Group; ZrCl4 was purchased from Maclean, 2-aminoterephthalic acid was purchased from Maclean, and cellulose was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0037] The composite separation membrane of the present invention is used to test the separation performance of oil-water mixture:

[0038] (1) Water flux test method: The water flux of the membrane is determined by the time it takes for 100 ml of pure water to pass through the composite membrane using a vacuum filtration device. The specific formula is:

[0039] In the formula, V(L), A(m 2 ), Δt(h) are the filtrate volume, effective membrane permeation area and filtration time respectively.

[0040] (2) Oil flux test method: The water flux of the membrane is determined by the time it takes for 100 ml of water-in-oil emulsion (kerosene emulsion, which is prepared by adding 990 ml of deionized water to a container and taking 30 mg of SDS as an emulsifier; then, adding 10 ml of kerosene to the above solution, ultrasonically stirring for 30 min, and then vigorously stirring for 6 h to obtain a surfactant-stabilized emulsion) to pass through the composite membrane using a vacuum filtration device. The specific formula is

[0041] Where V(L), A(m2), Δt(h), and ΔP(bar) are the filtrate volume, effective membrane permeation area, filtration time, and transmembrane pressure, respectively.

[0042] (3) Retention rate test method: Use a vacuum filtration device to pass 100 ml of water-in-oil emulsion (kerosene emulsion, prepared as above) through the composite membrane, and then use an infrared oil meter to measure the concentration of the solution before and after filtration. The specific formula is:

[0043] Among them C i (mg / L) and C0 (mg / L) are the oil contents in the filtered and original feed emulsions, respectively.

[0044] (4) Flux recovery rate test method: After filtering 100 ml of kerosene using a vacuum filtration device, the membrane was simply cleaned and the water flux was measured again. The formula is:

[0045] Among them, J W1 and J W2 are the pure water fluxes before and after filtering the emulsion, respectively.

[0046] Example 1

[0047] (1) Take a clean beaker, add 50 ml of DMF, 1 mmol of ZrCl4 and 1 mmol of H2ATA, then add 7 ml of acetic acid solution while ultrasonicating for 15 min.

[0048] (2) The prepared solution was poured into a 100 mL autoclave and reacted at 125° C. for 24 hours. After the reaction was completed, the solution was centrifuged to obtain the desired yellow crystalline solid, which was then washed several times with DMF and ethanol, and then the crystals were baked at 80° C. for 12 hours.

[0049] (3) The obtained yellow crystals and 100 mg of ZnO nanoparticles were added to 50 ml of ethanol solution, and then subjected to 60 W ultrasonic treatment for 70 min. The mixed solution after ultrasonic treatment was baked at 80 ° C for 12 h to obtain a composite material, which was then ground into 1300 mesh in a mortar to reduce its agglomeration phenomenon, and then collected to obtain MOF@ZnO material.

[0050] (4) 0.1 g MOF@ZnO was dispersed in 40 ml NN dimethylacetamide and magnetically stirred at room temperature for 20 min. Then 0.1 g polyvinyl pyrrolidone (molecular weight 111.1418) was added and magnetic stirring was continued at room temperature for 20 min. Then, ultrasonic treatment was performed for 10 min to obtain a mixed solution.

[0051] (5) 3 g of polyvinylidene fluoride powder was added to the mixed solution and then magnetically stirred at 70°C for 5 h. After mixing into a uniform casting solution, the solution was allowed to stand for degassing for 12 h.

[0052] (6) Use a 100 μm scraper to slowly move the casting liquid on the glass plate and then put it into deionized water to form a membrane. After soaking for 10 minutes, take it out and wash it to obtain an ultrafiltration membrane (thickness of 100 μm).

[0053] (7) The obtained ultrafiltration membrane was immersed in a 100 mg / L cellulose solution containing Tris-HCl buffer at room temperature for 2 h.

[0054] (8) The ultrafiltration membrane was repeatedly washed several times with deionized water to remove the residual organic solvent. The SEM image of the composite membrane is shown in Figure 1 .

[0055] Example 2

[0056] (1) Take a clean beaker, add 60 ml of DMF, 1.5 mmol of ZrCl4 and 1.5 mmol of H2ATA, then add 7 ml of acetic acid solution while ultrasonicating for 15 min.

[0057] (2) The prepared solution was poured into a 100 mL autoclave and reacted at 135° C. for 24 hours. After the reaction was completed, the solution was centrifuged to obtain the desired yellow crystalline solid, which was then washed several times with DMF and ethanol, and then the crystals were baked at 90° C. for 12 hours.

[0058] (3) The obtained yellow crystals and 120 mg of ZnO nanoparticles were added to 50 ml of ethanol solution, and then subjected to 60 W ultrasonic treatment for 80 min. The mixed solution after ultrasonic treatment was baked at 90 °C for 12 h to obtain a composite material, which was then ground into 1300 mesh in a mortar to reduce its agglomeration phenomenon, and then collected to obtain MOF@ZnO material.

[0059] (4) 0.1 g MOF@ZnO was dispersed in 40 ml NN dimethylacetamide and magnetically stirred at room temperature for 20 min. Then 0.1 g polyvinyl pyrrolidone (molecular weight 111.1418) was added and magnetic stirring was continued at room temperature for 20 min. Then, ultrasonic treatment was performed for 10 min to obtain a mixed solution.

[0060] (5) 3 g of polyvinylidene fluoride powder was added to the mixed solution and then magnetically stirred at 50° C. for 7 h. After being mixed into a uniform casting solution, it was allowed to stand for degassing for 14 h.

[0061] (6) Use a 150 μm scraper to slowly move the casting solution on the glass plate and then put it into deionized water to form a membrane. After soaking for 15 minutes, take it out and wash it to obtain an ultrafiltration membrane (thickness 150 μm).

[0062] (7) The obtained ultrafiltration membrane was immersed in a 120 mg / L cellulose solution containing Tris-HCl buffer at room temperature for 2 h.

[0063] (8) The ultrafiltration membrane was repeatedly washed several times with deionized water to remove the residual organic solvent.

[0064] Example 3

[0065] (1) Take a clean beaker, add 65 ml of DMF, 2 mmol of ZrCl4 and 2 mmol of H2ATA, then add 7 ml of acetic acid solution while ultrasonicating for 15 min.

[0066] (2) The prepared solution was poured into a 100 mL autoclave and reacted at 140° C. for 24 hours. After the reaction was completed, the solution was centrifuged to obtain the desired yellow crystalline solid, which was then washed several times with DMF and ethanol, and then the crystals were baked at 100° C. for 12 hours.

[0067] (3) The obtained yellow crystals and 150 mg ZnO nanoparticles were added to 60 ml of ethanol solution, and then ultrasonic treatment was carried out for 90 min. The mixed solution after ultrasonication was baked at 90 °C for 12 h to obtain a composite material, which was then ground into 1300 mesh in a mortar to reduce its agglomeration phenomenon, and then collected to obtain MOF@ZnO material.

[0068] (4) 0.1 g MOF@ZnO was dispersed in 40 ml NN dimethylacetamide and magnetically stirred at room temperature for 20 min. Then 0.1 g polyvinyl pyrrolidone (molecular weight 111.1418) was added and magnetic stirring was continued at room temperature for 20 min. Then, ultrasonic treatment was performed for 10 min to obtain a mixed solution.

[0069] (5) 3 g of polyvinylidene fluoride powder was added to the mixed solution and then magnetically stirred at 60° C. for 8 h. After being mixed into a uniform casting solution, it was allowed to stand for degassing for 16 h.

[0070] (6) Use a 150 μm scraper to slowly move the casting solution on the glass plate and then put it into deionized water to form a membrane. After soaking for 20 minutes, take it out and wash it to obtain an ultrafiltration membrane.

[0071] (7) The obtained ultrafiltration membrane was immersed in a 150 mg / L cellulose solution containing Tris-HCl buffer at room temperature for 2 h.

[0072] (8) The ultrafiltration membrane was repeatedly washed several times with deionized water to remove the residual organic solvent.

[0073] The MOF@ZnO@Cellulose@PVDF composite separation membrane prepared in Example 1 was used to test the separation performance of oil-water mixture. Edible oil, n-hexane, kerosene, and petroleum ether were used as water-in-oil emulsions (990 mL of deionized water was added to the container, and 30 mg of SDS was taken as an emulsifier; then, 10 mL of the corresponding oil was added to the above solution, ultrasonically stirred for 30 min, and then vigorously stirred for 6 h to obtain a surfactant-stabilized emulsion). Figure 2 It can be concluded that the MOF@ZnO@Cellulose@PVDF composite separation membrane has good separation efficiency.

[0074] The MOF@ZnO@Cellulose@PVDF composite separation membrane prepared in the example was taken to test its water flux. The filtration effect on oil and the flux recovery rate are shown in Table 1 below.

[0075] Table 1

[0076] <![CDATA[Water flux (L / m 2 ·h)]]> <![CDATA[Oil flux (L / m 2 ·h)]]> Retention rate (%) Flux recovery rate (%) Example 1 2980 700.2 99.2 98.6 Example 2 2750 680.7 98.6 97.9 Example 3 2800 676.2 98.8 98.4

[0077] Comparative Example 1

[0078] (1) Take a clean beaker, add 65 ml of DMF, 2 mmol of ZrCl4 and 2 mmol of H2ATA, then add 7 ml of acetic acid solution while ultrasonicating for 15 min.

[0079] (2) The prepared solution was poured into a 100 mL autoclave and reacted at 140° C. for 24 hours. After the reaction was completed, the solution was centrifuged to obtain the desired yellow crystalline solid, which was then washed several times with DMF and ethanol, and then the crystals were baked at 100° C. for 12 hours.

[0080] (3) The obtained yellow crystals were added to 60 ml of ethanol solution, and then subjected to ultrasonic treatment for 90 min, and then baked at 90 °C for 12 h to obtain a composite material, which was then ground to 1300 mesh in a mortar to reduce agglomeration, and then collected to obtain the MOF material.

[0081] (4) 0.1 g MOF was dispersed in 40 ml NN dimethylacetamide and magnetically stirred at room temperature for 20 minutes, then 0.1 g polyvinyl pyrrolidone (molecular weight 111.1418) was added and magnetic stirring was continued at room temperature for 20 minutes, followed by ultrasonic treatment for 10 minutes to obtain a mixed solution.

[0082] (5) 3 g of polyvinylidene fluoride powder was added to the mixed solution and then magnetically stirred at 60° C. for 8 h. After being mixed into a uniform casting solution, it was allowed to stand for degassing for 16 h.

[0083] (6) Use a 150 μm scraper to slowly move the casting solution on the glass plate and then put it into deionized water to form a membrane. After soaking for 20 minutes, take it out and wash it to obtain an ultrafiltration membrane.

[0084] (7) The obtained ultrafiltration membrane was immersed in a 150 mg / L cellulose solution containing Tris-HCl buffer at room temperature for 2 h.

[0085] (8) The ultrafiltration membrane was repeatedly washed several times with deionized water to remove the residual organic solvent.

[0086] Comparative Example 2

[0087] (1) 0.1 g ZnO was dispersed in 40 ml NN dimethylacetamide and magnetically stirred at room temperature for 20 minutes, then 0.1 g polyvinyl pyrrolidone (molecular weight 111.1418) was added and magnetically stirred at room temperature for another 20 minutes, followed by ultrasonic treatment for 10 minutes to obtain a mixed solution.

[0088] (2) 3 g of polyvinylidene fluoride powder was added to the mixed solution and then magnetically stirred at 60° C. for 8 h. After being mixed into a uniform casting solution, it was allowed to stand for degassing for 16 h.

[0089] (3) Use a 150 μm scraper to slowly move the casting liquid on the glass plate and then put it into deionized water to form a membrane. After soaking for 20 minutes, take it out and wash it to obtain an ultrafiltration membrane.

[0090] (4) The obtained ultrafiltration membrane was immersed in a 150 mg / L cellulose solution containing Tris-HCl buffer at room temperature for 2 h.

[0091] (8) Wash the ultrafiltration membrane repeatedly with deionized water several times to remove the residual organic solvent.

[0092] Comparative Example 3

[0093] On the basis of Example 3, no cellulose was added, and other conditions were the same as Example 3.

[0094] The water flux was tested, and the filtering effect on oil and the flux recovery rate are shown in Table 2.

[0095] Table 2

[0096]

[0097] As can be seen from Table 2, the MOF@ZnO@Cellulose@PVDF composite separation membrane prepared in Example 3 was tested for oil-water mixture separation performance with Comparative Examples 1, 2, and 3, and kerosene was used as the water-in-oil emulsion. As shown in Table 2, MOF@ZnO@Cellulose@PVDF has a unique octahedral structure and can load nanoparticles on its framework, which greatly improves the oil-water separation performance and stability of the composite membrane. In addition, the addition of the hydrophilic organic coating can more firmly embed the composite particles in the membrane. The hydrophilicity of the hydrophilic organic coating membrane is greatly increased, which provides an effective basis for practical applications.

[0098] The integration of MOF and ZnO not only solves the problem of MOF's limited number of active sites and limited catalytic reaction types, but also solves the defect of ZnO's easy aggregation during the reaction process, effectively synergizing the respective advantages of ZnO and MOF, and broadening the scope of their application reactions and prospects. Therefore, ZnO / MOF composite materials have very broad prospects.

[0099] Comparative Example 4

[0100] On the basis of Example 1, the concentration of added cellulose was 50 mg / L, and other conditions were the same as Example 1.

[0101] Comparative Example 5

[0102] On the basis of Example 1, the concentration of added cellulose was 150 mg / L, and other conditions were the same as Example 1.

[0103] Comparative Example 6

[0104] On the basis of Example 1, the concentration of added cellulose was 200 mg / L, and other conditions were the same as Example 1. See Table 3 for the performance measurement results.

[0105] Table 3

[0106]

[0107] It can be seen that when the cellulose content is lower than 100 mg / L, the hydrogel solution formed cannot form a hydration layer on the membrane surface, and cannot increase the hydrophilicity and separation efficiency of the membrane; when it is higher than 100 mg / L, the coating formed on the surface of the cellulose solution cannot form a synergistic reaction with the composite particles, resulting in poor overall performance.

[0108] The preparation method of the hydrophilic oil-water separation membrane provided by the present invention has the following main principles: in the pore-forming method, pores are formed by using a pore-forming agent polyvinyl pyrrolidone, and particles are embedded in the pores of the membrane. Because the MOF material has a unique octahedral structure, ZnO nanoparticles can be better loaded on the MOF metal frame, and the addition of a hydrophilic organic coating can embed the composite particles more firmly in the membrane without loss due to the number of filtrations, so the prepared membrane can achieve a good effect in oil-water separation.

[0109] The technical problem to be solved by the present invention is to provide a preparation method of a MOF@ZnO@Cellulose@PVDF composite membrane and its application. The method has a simple preparation process and low material price, and is suitable for industrial production. The obtained composite membrane has the characteristics of high strength and high flux. In the oil-water separation process, the flux is stable and the separation performance is excellent. It has wide industrial application value in oil-water separation, sewage treatment and marine oil spills.

[0110] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a composite film coated with cellulose, characterized in that: include, DMF, ZrCl4 and H2ATA were mixed, ultrasonicated, acetic acid was added, and the prepared solution was poured into an autoclave for high temperature reaction; After the reaction is completed, the solution is centrifuged to obtain a yellow crystalline solid, which is washed with DMF and ethanol and baked at high temperature to obtain a yellow crystalline solid; The yellow crystalline solid and ZnO nanoparticles were dispersed in an ethanol solution, ultrasonically mixed, dried, and ground to obtain MOF@ZnO material; MOF@ZnO was dispersed in NN-dimethylacetamide and stirred, polyvinyl pyrrolidone was added and continued to stir, and ultrasonic treatment was performed to obtain a mixed solution; Adding polyvinylidene fluoride powder into the mixed solution, stirring and mixing evenly, and standing to degas, to obtain a casting solution; The casting solution is dip-coated on the carrier, and the dip-coated carrier is placed on a glass sheet and treated in deionized water to obtain an ultrafiltration membrane; The obtained ultrafiltration membrane was immersed in a cellulose solution containing Tris-HCl buffer solution to obtain a MOF@ZnO@Cellulose@PVDF composite separation membrane.

2. The preparation method according to claim 1, characterized in that: The material ratio of DMF, ZrCl4 and H2ATA is 50mL:(0.5~2mmol):(0.5~2mmol).

3. The preparation method according to claim 1 or 2, characterized in that: The ratio of acetic acid to DMF is 5-7 mL:50 mL.

4. The preparation method according to claim 1, characterized in that: The prepared solution is poured into an autoclave for high temperature reaction, wherein the reaction temperature is 120-125° C. and the reaction time is 12-24 hours.

5. The preparation method according to claim 1, characterized in that: The yellow crystalline solid obtained by the high-temperature baking is processed at a temperature of 80° C. for a time of 10 to 12 hours.

6. The preparation method according to claim 1, characterized in that: The yellow crystalline solid and ZnO nanoparticles are dispersed in an ethanol solution, wherein the material ratio of the MOF material to the ZnO is (0.1-0.9):(0.1-0.9).

7. The preparation method according to claim 1, characterized in that: In the mixed solution, the ratio of MOF@ZnO, NN dimethylacetamide and polyvinyl pyrrolidone is 0.1 g:40 ml:0.1 g, and the particle size of MOF@ZnO is 1300 mesh.

8. The preparation method as claimed in claim 1 or 7, characterized in that: The ratio of the mixed liquid to polyvinylidene fluoride is (30-50) ml: (3-4) g.

9. The preparation method according to claim 1, characterized in that: The cellulose solution of the Tris-HCl buffer solution has a pH value of 8.5 and a cellulose concentration of 80-100 mg / L.

10. Use of the composite membrane prepared by the preparation method according to any one of claims 1 to 9 in oil-water separation, characterized in that: The oil includes kerosene.

Citation Information

Patent Citations

  • Preparation method of MOF (metal organic framework)-loaded ZnO scale inhibition ultrafiltration membrane

    CN108854569A

  • Self-supporting MOF membranes

    CN109195700A

  • MOF / ZnO composite material and preparation method and application of working electrode of MOF / ZnO composite material

    CN114019001A

  • Preparation method of hydrophilic oil-water separation anti-pollution membrane, anti-pollution membrane and application of anti-pollution membrane

    CN117138593A

  • High Flux Fluid Separation Membranes Comprising a Cellulose or Cellulose Derivative Layer

    US20090078640A1